Recommendations for the Use of Prolonged‐Release Fampridine in Patients with Multiple Sclerosis (MS). (22nd April 2013) - Preiningerova, Jana Lizrova; Baumhackl, Ulf; Csepany, Tunde; Czaplinski, Adam; Deisenhammer, Florian; Derfuss, Tobias; Fabjan, Tanja H.; Fazekas, Franz; Fuchs, Siegrid; Havrdova, Eva; Ledinek, Alenka Horvath; Illes, Zsolt; et al.
Summary Prolonged‐release fampridine (fampridine PR) is a potassium channel blocker that improves conductivity of signal on demyelinated axons in central nervous system. Fampridine PR has been approved to improve speed of walking in patients with multiple sclerosis. This statement provides a brief summary of data on fampridine PR and recommendations on practical use of the medication in clinical practice, prediction, and evaluation of response to treatment and patient management.